Deformation and fracture mechanics of engineering materials - Hertzberg, Richard W. , 1937-; Hertzberg, Jason L. , 1969-; Vinci, Richard Paul (John Wiley & Sons, Inc., 2013)
"Hertzberg's 5th edition of Deformation & Fracture Mechanics of Engineering Materials offers several new features including a greater number and variety of homework problems using more computational software; more "real world" applications of theories, case studies; and less coverage of metals. Furthermore, this edition has more focus shifted toward emerging technologies (nanotechnology, micro mechanical systems), dislocations, macroscale plasticity; nanomaterials, biomaterials, smart materials and a new chapter on products liability/recall - supported by vast majority of survey respondents"-